THE INFLUENCE OF WORK LIFE BALANCE AND WORK FROM HOME ON WORK PRODUCTIVITY: A SYSTEMATIC LITERATURE REVIEW (SLR) - Ismawati, Ismawati; Soetjipto, Budi Eko; Sopiah, Sopiah (IJBLE Scientific Publications Community Inc., 2023)
This study develops the influence of organizational support on work productivity with systematic literature reviews that have been carried out as needed and beneficial to work life balance and work from home, with professional involvement that results in performance and responsibility in personal life can reduce conflict and is performance-based. The research method used uses two qualitative and quantitative approaches, in the form of a systematic literature review (SLR) using PRISMA and bibliometric analysis using the VOSviewer application. With the results of research WFH has a significant positive impact on individual emotional well-being and balance, increasing happiness, reducing emotional sensitivity, and increasing time efficiency and productivity. Good management and a balanced approach are essential to ensure the implementation of WFH provides maximum benefits to individuals and organizations. The success of WFH depends on the ability to overcome these challenges and create a productive and healthy work environment for all parties involved. WLB and the implementation of policies that support employees' work-life balance, such as flexibility in time, location, work schedules, and leave provisions.